Cardiac Development in Zebrafish and Human Embryonic Stem Cells Is Inhibited by Exposure to Tobacco Cigarettes and E-Cigarettes - Palpant, Nathan J. (PLoS One, 2015)
BACKGROUND: Maternal smoking is a risk factor for low birth weight and other adverse developmental outcomes. OBJECTIVE: We sought to determine the impact of standard tobacco cigarettes and e-cigarettes on heart development in vitro and in vivo. METHODS: Zebrafish (Danio rerio) were used to assess developmental effects in vivo and cardiac differentiation of human embryonic stem cells (hESCs) was used as a model for in vitro cardiac development. RESULTS: In zebrafish, exposure to both types of cigarettes results in broad, dose-dependent developmental defects coupled with severe heart malformation, pericardial edema and reduced heart function. Tobacco cigarettes are more toxic than e-cigarettes at comparable nicotine concentrations. During cardiac differentiation of hESCs, tobacco smoke exposure results in a delayed transition through mesoderm. Both types of cigarettes decrease expression of cardiac transcription factors in cardiac progenitor cells, suggesting a persistent delay in differentiation. In definitive human cardiomyocytes, both e-cigarette- and tobacco cigarette-treated samples showed reduced expression of sarcomeric genes such as MLC2v and MYL6. Furthermore, tobacco cigarette-treated samples had delayed onset of beating and showed low levels and aberrant localization of N-cadherin, reduced myofilament content with significantly reduced sarcomere length, and increased expression of the immature cardiac marker smooth muscle alpha-actin. CONCLUSION: These data indicate a negative effect of both tobacco cigarettes and e-cigarettes on heart development in vitro and in vivo. Tobacco cigarettes are more toxic than E-cigarettes and exhibit a broader spectrum of cardiac developmental defects.